Peran Polri dalam Penanganan Kejahatan Jalanan (Klitih) yang Melibatkan Anak di Wilayah Hukum Polda Derah Istimewa Yogyakarta - Rafi Ardian Syahputra, Muhammad; Qorina Pangestika, Elza (Green Publisher Indonesia, 2025)
Crime on the streets has become a social phenomenon that is increasingly troubling the community in the Special Region of Yogyakarta. Many of the perpetrators came from underage students. Klitih, which originates from various environmental influences and adolescent social behavior, has resulted in serious injuries to death. The purpose of this study is to analyze the role of the National Police in handling street crimes involving children in the jurisdiction of the Special Region of Yogyakarta Police. This study uses empirical research. The data collection technique was an interview with members of the Directorate of General Criminal Investigation of the Special Region of Yogyakarta. The data analysis used in this study is a descriptive analysis with a qualitative approach. The results of this study show that the role of the National Police is very important in dealing with street crime through pre-emptive, preventive, and repressive efforts. Pre-emptive efforts are carried out through sambaing activities, coaching and distribution, character development, coaching profiling, and coordination with related agencies. Preventive efforts by carrying out patrols and forming a special team to handle street violence crimes. Repressive efforts are carried out by investigative actions, cooperation with other police stations, pursuits and arrests, and examinations. The factors that affect street crime are internal factors and external factors.